A few remarks on the utility of visual motion perception to assess the integrity of the magnocellular system or the dorsal stream. (June 2016) - Skottun, Bernt C.
Abstract: It has been proposed that visual motion perception may be used to assess magnocellular or dorsal stream integrity. It is here pointed out, based on recently published data from dyslexic readers, that it is possible for deficient motion perception to exist without there being deficiencies in neither the magnocellular system nor in the dorsal stream. This makes it difficult to rely upon tests of motion perception to assess the integrity of these structures.